Cost-Benefit Analysis: Nutritious Food as Medication in Healthcare Insurance Coverage - Kolappapillai, Balasubramaniam (Digital Repository of Theses - SSBM Geneva, 2024)
Today lifestyle of all economic centric individuals handling healthcare expenditure has drastically gone up post COVID-19 known as Corona Virus that broke up in 2020 onwards, This research proposal focus the discussion on expansion of insurance coverage towards awareness on nutritious food as medication and effective physical activities along efficient competencies in economic crisis management through healthcare insurance benefits coverage for each service in India so that individuals health care commands reduced medical cost at crisis in almost every developing country addressing such economic crisis. Increased awareness about health benefits through natural food source and physical activities to keep the internal healing & autoimmune system effectively helps human capital in life model established in current corporate live style.